The Positive Impact of Organizational Trust: a Systematic Review - Idha Rahayuningsih (Journal of Educational, Health and Community Psychology, 2019)
The critical role of trust is to strengthen working relationships to ensure that organizations achieve their goals effectively. This study aims to explore the positive impact of organizational trust, namely trust towards colleagues, employers, and organization. We conducted a systematic review following the PRISMA guideline, highlighting the number of records that were identified, screened, assessed for eligibility, and included for the study. The literature search was conducted online by using the keyword "Organizational Trust" on three platforms, namely ScienceDirect, Sage, and ProQuest. We selected 30 research articles that use organizational trust as either a dependent, mediating or moderating variable. Next, we reviewed and assessed the papers according to their research objectives, role/function of the variable, authors, year of publication, number of subjects/research samples and findings. Findings show: (1) organizational trust can reduce turnover tendency, as well as increase the intention to stay at the organization, effectiveness of communication within the organization, change readiness, continuum improvement, innovative behavior, job satisfaction, organizational citizenship behavior (OCB), organizational commitment, safety motivation, and work performance; (2) As an independent variable, trust in coworkers could impact joint learning activities, willingness to share knowledge and ideas with coworkers, networking commitment, job satisfaction, and organizational commitment; (3) Trust in superiors reinforces organizational identification, work performance (the strongest level of positive correlation), job satisfaction, organizational citizenship behavior, organizational commitment as well as a predictor of burnout and depersonalization.